Phytochemicals and pharmacology of pomegranate (Punica granatum L.): nutraceutical benefits and industrial applications: a review - Noreen, Sana; Hashmi, Bushra; Aja, Patrick Maduabuchi; Atoki, Ayomide Victor (Frontiers in Nutrition, 2025)
IntroductionPomegranate (Punica granatum L.) is a fruit native to South Asia and currently can grow in tropical and subtropical areas, which produces approximately seven thousand metric tons per year. Pomegranate stands out for its rich flavor and functional properties, which is why it has gained acceptance in different countries. Beyond its health advantages, it has industrial applications in food technology, cosmetics, and medicines. This study focuses on its diverse phytochemical profile and the medicinal properties of its bioactive components.MethodsA search in PubMed, Scopus, EBSCO, Medline, PubMed, Embase, SID, and Iran Medex databases was conducted to identify clinical and observational studies on Pomegranate consumption and its industrial uses.ResultsPomegranate and its by-products are rich in beneficial phytochemicals, provide health benefits, and help manage ailments. Sustainable reuse of its by-products supports health, economic growth, and food security.ConclusionPomegranate provide health benefits, including antidiabetic, antioxidant, anticancer, and anti-inflammatory effects, with potential for food product development and disease management. Analyzing pomegranate's functional and nutritional properties, especially its peel and seed, is crucial for understanding the mechanisms involved in industrial processes for nutraceutical or functional food products.